2017
DOI: 10.4236/jtr.2017.52014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performances of Pure TB-Lamp Kit for <i>M. tuberculosis</i> Complex Detection in Sputum Samples

Abstract: Tuberculosis represents a main concern for public health worldwide. In poor countries, the most prevalent method for bacteriological confirmation remains Smear Sputum Microscopy (SSM). This study objective was to assess clinical performances of Loop Mediated Isothermal Amplification for TB detection (Lamp-TB). Sputum of patients presenting symptoms consistent with tuberculosis were collected according to the National Tuberculosis Control Programme guidelines in Centre Antituberculeux de Yopougon. SSM after Zie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…69 According to research, 68 the sensitivity of the test is 55.6% in patients with a negative smear and 98.2% in patients with a positive smear. According to N'guessan et al, 6 the PURE-LAMP test has a greater sensitivity than that of smear microscopy. However, the specificity of the smear microscopy was greater than that of PURE-LAMP.…”
Section: Pure-lampmentioning
confidence: 99%
See 1 more Smart Citation
“…69 According to research, 68 the sensitivity of the test is 55.6% in patients with a negative smear and 98.2% in patients with a positive smear. According to N'guessan et al, 6 the PURE-LAMP test has a greater sensitivity than that of smear microscopy. However, the specificity of the smear microscopy was greater than that of PURE-LAMP.…”
Section: Pure-lampmentioning
confidence: 99%
“…5 Alternatively, Lowenstein-Jensen culture, which is often considered the gold standard in presumptive respiratory infections, looks to be more specific than smear microscopy, however, it is more timeconsuming (4-8 weeks in culture). It demands appropriate infrastructure and possibly the best laboratory personnel 6 which can cause delays in efficient medical treatments. Therefore, the demand for novel, quick, and reliable diagnostic procedures has arisen.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a positive result by this test does not discriminate between the Mycobacterium species [ 7 ]. Otherwise, Lowenstein-Jensen culture, generally used as the gold standard in suspected pulmonary cases, is more sensitive than smear microscopy, but it is time consuming (may take 4–8 weeks in solid media culture), and it requires adapted infrastructures and well-trained laboratory staff [ 8 ], which can delay effective medical interventions; therefore, the need for new rapid and accurate diagnostic methods has emerged. With the rapid evolution of molecular techniques, a wide variety of nucleic amplification tests (NAATs) such as polymerase chain reaction (PCR), real-time PCR, and loop-mediated isothermal amplification (LAMP), are available for the diagnosis of TB .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that PURE-LAMP has very high sensitivity and specificity, which makes it economic, cost effective and rapid method for the diagnosis of tuberculosis [ 8 , 89 ]. Mitarai et al [ 88 ] reported the sensitivity of PURE-LAMP in smear-negative TB patients to be 55.6%, and 98.2% among smear positive TB patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation